Efektivitas Pendekatan Saintifik Dalam Peningkatan Kompetensi Numerasi Pada Materi Suhu Di SMP Negeri 41 Surabaya - Endang Sri Wahjuningsih (PGRI Provinsi Jawa Timur, 2022)
This study aims to determine the effectiveness of a scientific approach in improving numeracy competence on the topic of temperature in junior high school students. The research was conducted at SMP Negeri 41 Surabaya, with 32 students from class VII-A in the first semester of the 2022/2023 academic year. The study used a quasi-experimental design with a pre-test and post-test control group. The experimental group was taught using a scientific approach, while the control group was taught using a conventional approach. The data collected were analyzed using a t-test. The results of the study showed that there was a significant difference in the post-test scores of the experimental and control groups, with a mean score of 87.5 for the experimental group and 75.6 for the control group. This indicates that the scientific approach is effective in improving numeracy competence on the topic of temperature in junior high school students. Therefore, it is recommended that teachers use a scientific approach to teach the topic of temperature to improve students' numeracy competence.